Harrison's neurology in clinical medicine - Harrison, Tinsley Randolph, 1900-1978; Hauser, Stephen L; Josephson, Scott Andrew (New York : McGraw-Hill Medical, 2010)
"This book provides an easy-to-use format and full coverage of the most authoritative information available anywhere of clinically important topics in neurology and psychiatry, while retaining the focus on pathophysiology and therapy that has always been characteristic of Harrison's Principles of Internal Medicine"--Provided by publisher
"Derived from Harrison's principles of internal medicine, 17th edition"--P. facing t.p
Includes bibliographical references and index
1 13
Keywords: Nervous system -- Diseases; Neurology